Perspektif Baru dalam Teori Kualitas Pelayanan: Pentingnya Intensi Studi pada Perusahaan Fintech di Indonesia - Jokhu, Jean Richard; Armando, Arnold (Manajemen Bisnis Kompetensi, 2018)
The development of fintech-based companies has become one of the issues in the challenges of globalization. Research that has questioned this strategic issue has not answered why fintech companies manage consumers. This research tries to offer a new perspective in managing consumers in fintech companies. By introducing Intention theory which was first presented as marketing ‘output’ this research offered the intention as a moderator of the relationship of knowledge to service quality obtained by consumers in fintech companies. The conclusion of this study is that the quality of services obtained by consumers can increase along with the strengthening of consumer intentions in using a fintech service or product. Keywords: service quality, knowledge, intention